The Effect of Poster Media on Student Learning Outcomes in IPAS Subjects in Grade IV of SD Negeri 25 Sungai Pinyuh - Farida, Farida; Risdianna Andika Fatmawati; Riyanti Nurdiana (PT. ALHAFI BERKAH INDONESIA, 2025)
This study aims to determine the effect of poster media on the learning outcomes of fifth grade students of SDN 25 Sungai Pinyuh. The research method used is the experimental method while the research design used, namely pree experimental design. The sample included in this research, namely grade V students of SDN 25 Sungai Pinyuh, totaling 18 students consisting of 8 male students and 10 female students. the technique used to determine the experimental class uses the learning outcomes test data collection technique. In data collection using tests, and documentation. Hypothesis testing uses the t test formula (independent samples test) which is preceded by an analysis prerequisite test, namely the normality test. The results showed that there was a significant difference in student learning outcomes before and after using poster media. This is indicated by the results of the t test with a significant level of 5% or 0.05. The average pretest score was 46.1 and the average posttest score was 78.0, which was better than the pretest at the specified KKM of 75.